Surgical Aspects of Implantology - Lutz, Rainer; Kesting, Marco Rainer (Springer Berlin Heidelberg, 2023)
Dental implants are the means of choice for surgical tooth replacement. Titanium and titanium alloys have proven themselves as implant materials over decades. In addition, implants made of zirconium oxide ceramics are successfully used clinically. Immunologically controlled processes lead to osseointegration of the implants. Preoperative diagnostics allow for planning of the prosthetically ideal implant position so that implant placement can be performed with a high degree of certainty. In case of insufficient bone conditions due to jaw atrophy, traumatic bone loss or after tumor resections, augmentations of the hard and soft tissues are often necessary. Additional surgical measures of the peri-implant soft tissues may also be necessary to ensure long-term survival of the implants. The control of possible complications is essential to ensure a safe therapy of the patients for the elective procedures.
CRIS-Team Scopus Importer:2023-09-29